(untitled) (International Journal of Economics Management and Social Science, 2026)
Background: The relationship between law, social norms, justice, and judicial effectiveness is one of the central preoccupations of sociology of law, a field that examines legal systems not as autonomous normative orders but as socially embedded institutions shaped by and reciprocally shaping social structures, cultural values, and power relations. Objective: This study analyzes the relationships between social norms, justice, and judicial system effectiveness through a sociology of law framework, drawing on diverse theoretical traditions within the field. Methods: A systematic literature review was conducted using Scopus, Web of Science, and Google Scholar, covering peer-reviewed publications from 2019 to 2025 on sociology of law, legal pluralism, judicial effectiveness, access to justice, and social norms. Results: The findings reveal that legal systems achieve effectiveness not through formal conformity to procedural rules alone but through their alignment with prevailing social norms, their capacity to deliver socially recognized justice, and their accessibility to all social strata. Legal pluralism, public legal consciousness, and the sociology of access to justice are identified as key analytical frameworks. Conclusion: A sociology of law approach offers essential insights for judicial reform by foregrounding the social embeddedness of law and demonstrating that judicial effectiveness requires cultural legitimacy, normative resonance with community values, and structural equity of access. Keywords: sociology of law, social norms, justice, judicial effectiveness, legal pluralism, access to justice, legal consciousness